Mobile Technical Calculators with a Flipped Classroom for Sustainability Machining Process - Rahmat Setiadi, Bayu; Sukardi, Thomas; ., Sugiyono (International Journal of Engineering and Technology, 2018)
This study has the primary objective in planning machining practices early on through the precision of machining parameter analysis with mobile technical calculators combined with the flipped classroom. This research will compare the calculations with manual and mobile phone devices and measure the effectiveness of the media concerning the three elements of sustainable development, i.e., economic, environmental, and social. The research used posttest-control design experiment design which was divided by random sampling. The sampling technique uses saturated sampling. Data collection using performance test, observation, and questionnaire. Data analysis using independent sample test. The results show the use of mobile technical calculator with a flipped classroom is more effective in generating the accuracy of analysis than manual analysis. The t-test results state that there is a difference if this media is applied in machining practice. Also, students' perspectives on the application of these auxiliary media analyzes have an increasing impact on sustainable machinery processes concerning elements in sustainable development.Â Â